ANALISIS FAKTOR-FAKTOR PERILAKU HIDUP BERSIH DAN SEHAT YANG BERHUBUNGAN TERHADAP KEJADIAN COVID-19 PADA MASYARAKAT DI WILAYAH KERJA UPTD PUSKESMAS PENGASINAN KOTA DEPOK TAHUN 2021-2022 - Ardi Pangestu; Azhar Pherdinand Abdillah; Erlangga Sulaeman; Ichsan Al Kautsar; Siti NurSehha; Zahira Hananda Naila Rozni (Jurnal Inovasi Penelitian, 2022)
19 sufferers to take oxygen or risk shortness of breath. The order of Clean and Healthy Living Behavior in the household is the most important point during the Covid-19 pandemic. Therefore, if smoking behavior is applied continuously, there is a risk of complications and death. This study was conducted with the aim of knowing the general description of the state of public health status based on aspects of implementing Clean and Healthy Lifestyles in the community to prevent the transmission of Covid-19 in the UPTD Area of ​​the Pengasinan Health Center, Depok City. This study uses a descriptive analytical method which aims to identify health problems, the causes of health problems and provide alternative solutions to health problems or the less than optimal implementation of the Health Service Program in a health service agency. The data presented in the form of numbers in the form of secondary data collection (Depok Health Profile). The results of this study there are 1,637 (27%) who smoke in the house and there are 4,509 (73%) who do not smoke in the house. The conclusion of this study is the identification of the problem obtained from the results of secondary data that has been obtained from the UPTD Pengasinan Health Center Depok City, namely there are still many people around the UPTD Pengasinan Health Center Work Area who smoke in the house. Suggestions from this research are expected that people in the city of Depok, West Java can reduce smoking behavior in order to reduce the severity of Covid-19